Chagas da exclusão: internação compulsória e Leprosário do Padre Bento (São Paulo 1930-1986) - Rodrigues, Ivan Canoletto (2016)
This research deals with the compulsory hospitalization of leprosy in São Paulo, as well as the factors that led to the institutionalization of this process, its influence on the national scene and its consequences for the people directly affected by it. Besides, it presents everyday elements of a leprosarium, taking as object the Sanatorium Padre Bento, in Guarulhos, considered a reference in the nursing homes colonies system (leprosariums). Compulsory admissions intensified from 1930, extending through 1986. However, its consequences reverberate to the present day, matter of fact the hospitalized people had their families dismantled, spent many years isolated from society and still suffer from the stigma of the disease, making it difficult in much social reintegration after the release of leprosariums, causing some chose to continue living in the accommodation of these institutions. In the 1930s, little was known about the modes of transmission of leprosy. The only known vector was the patient himself, causing the incarceration and stigma were presented as a necessity in the fight against leprosy. Meantime, the research indicates that the reasons for such a measure were not strictly medical, with influence of hygienist medicine and even eugenic ideas, exclusion being used as a means of social "cleaning". This is related to the modernization and industrialization context that Brazil and, especially, São Paulo were passing through. Even with most of the leprosariums counting with great structure and the attempt of the inmates to have as close as possible to the everyday reality out there, there were many years of restriction of freedom without existence of a cure or treatment. The drastic consequences of this authoritarian measure caused the leprosy initiate a fight as a social movement, in seeking remedies from the State